Liquid-liquid extraction of cerium using synergist extractant - Hidayah, N. N.; Nurihan, M. F. S.; Sumaiya, Zainal Abidin (Faculty Mechanical Engineering, UMP, 2018)
This work studies on the performance of synergist extractants on the extraction of Cerium (Ce) alone. Conventional extractant, 4,4,4-trifluoro-1-(2-thienyl)-1,3- butanedione (HTTA) was combined with 3-methylimidazolium bis(triflouromethylsulfonyl)imide [Cnmim][NTf2], n=2,4 at different ratios to identify the best mixing ratio between HTTA and ionic liquid respectively. The effect of pH and temperature were also investigated on synergist extractant. Liquid-liquid extraction (LLE) was conducted by mixing synergist extractant with aqueous phase of Ce in the ratio of 1:1. The studies on pH and temperature were conducted in a range of 1.5 – 5.5 and 25 – 45oC respectively. synergist extractant of HTTA-[C4mim][NTf2] was found to have better extraction efficiency compared to HTTA-[C2mim][NTf2] under the optimum pH of 4.5 – 5.5 and temperature of 45°C. HTTA-[C4mim][NTf2] also exhibits better Ce extraction when the extractant was at independent mode i.e. HTTA or [C4mim][NTf2]. In conclusion, the synergist extractant is more efficient at extraction of Ce compared to independent extractant under the pH value of 5 at 45°C.